Make or break: The relationship between idiosyncratic volatility and stock returns in the Philippines - Li, Angeline (Animo Repository, 2021)
Economic settings, portfolio allocation, methodological approach, samples, and controlled variables can serve as factors affecting the relationship between idiosyncratic volatility (IVOL) and stock returns. A riskier transaction follows higher expected returns, indicating a positive relationship. Nonetheless, recent studies have observed a negative relationship that leads to the IVOL puzzle. However, previous studies had varying results, which used varying portfolio allocation, approaches, samples, and variables to explain the relationship between IVOL and stock returns. In addition, more studies are being conducted on developed countries relative to emerging countries. Hence, the study aims to assess the relationship between IVOL and stock returns in the Philippine financial market; an emerging market. The study would divide the data into 2 5-year interval time frames. It will focus on macroeconomic, financial, and investor-sentiment variables as controlled variables to assess the relationship. The Fama-French 3-Factor (FF3) Model will be used as the method to estimate IVOL, wherein portfolio excess returns is based on equally-weighted or value-weighted portfolio allocation. This is to obtain the relationship between expected returns and IVOL. Subsequently, a cross-sectional regression including the multidimensional variables will be done to postulate an explanation for the relationship. In this light, the results of the study show that there is no relationship between IVOL and stock returns in the Philippine financial market, using a methodological approach similar to the study of Ang et al. (2006). In contrast, when using the Fama-MacBeth approach, the relationship turns negative during 2010 to 2015, low sentiment periods, and when using the negative alpha sub-sample. In contrast, the relationship remains insignificant during 2016 to 2020 and high sentiment periods, while the relationship turns positive when using the positive alpha sub-sample under the Fama-MacBeth approach.